Impact of passive heat stress on persons with spinal cord injury: Implications for Olympic spectators. Issue 2 (2nd April 2020) - Trbovich, Michelle B.; Handrakis, John P.; Kumar, Nina S.; Price, Mike J.
ABSTRACT: Environmental heat stress can negatively impact health, work capacity, and athletic performance and potentially to lead to life-threatening consequences if not mitigated. With the upcoming Toyko Olympic games to be held during anticipated warm ambient temperatures (up to 29°C), and with spectators potentially spending long durations of time outdoors, certain populations of persons with impaired thermoregulatory capacity will be at higher risk of heat-related illness from passive heat stress. Persons with spinal cord injury (SCI) are one of these groups as a result of a decentralized sympathetic nervous system, which leaves them with impairment in convective and evaporative cooling via vasodilation and sweating, respectively. This review summarizes (1) thermoregulatory physiological responses of persons with SCI under passive heat stress: the effect of level and completeness of injury; (2) the impact of passive heat stress on quality of life (QOL), outdoor participation, behavioral thermoregulation, and cognition; (3) recommendations and education for clinicians providing health care for persons with SCI; and (4) suggestions of future directions for exploring the gaps in the literature on passive heat stress in persons with SCI. This article aims to equip consumers with SCI and health-care professionals with the most up-to-date knowledge on passive heat stress responses in persons with SCI, so that their attendance at the Olympic games can be done with maximal safety and enjoyment.